Urgensi Pelatihan Ekonomi Digital bagi Pekerja Anak: Studi Kasus Kecamatan Sragi, Pekalongan - Ari Arisman; Raisa Hilia Aini Syifa (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study examines the urgency of digital economy training as an effort to mitigate the phenomenon of child labor among school-age youth in Sragi District, Pekalongan Regency, Central Java. Using a qualitative case study approach with descriptive-analytical methods, this research explores the socio-economic conditions, motivations, and challenges faced by children aged 16–18 who work instead of pursuing formal education. Data were collected through semi-structured interviews, observation, and documentation involving several key informants, including child workers, community leaders, and local entrepreneurs. The findings reveal that economic pressure, family disharmony, and limited access to education are the primary factors driving school dropout and child labor. Nevertheless, most informants exhibit strong motivation to continue learning through non-formal education such as PKBM and show interest in digital economic activities, including e-commerce and freelance work. The study concludes that digital economy training can serve as an empowerment medium, enhancing human capital and providing sustainable livelihood alternatives for marginalized youth. These findings reinforce empowerment and human capital theories, emphasizing the need for community-based digital training integrated with non-formal education programs